Comparison of Parametric Indices of Anthropometric and Biomechanical Characteristics of Female Basketball Players, Volleyball Players and Handball Players - Ali Fatahi (Islamic Azad University, Hamedan Branch, 2021)
Objective: This study aimed to Compare parametric indices of anthropometric and biomechanical characteristics of female basketball, volleyball, and handball players. Methods: This research is purposive comparative-descriptive study. A total of 100 female students (35 handball players, 37 volleyball players, and 28 basketball players) participated in this study. The normality of the data distribution was examined using the Kolmogorov-Smirnov test. The Mean±SD and percentage rank to describe the information, multiple correlation coefficient to reduce the overlapping data, and analysis of the main components of the data to determine the leading indicators of anthropometric and biomechanical characteristics of female handball, volleyball, and basketball players and ANOVA was used to compare the corresponding leading indices in different age groups. Results: Ten parameters for female handball and volleyball players and nine parameters for female basketball players were highlighted as the leading indicators. Head width, leg length, ankle width, scapular fat for basketball and handball players, biceps and weight for handball and volleyball players, abdominal fat, leg length for volleyball and basketball players, and height introduced as the leading common indicators among all groups of players. The results related to the variance extracted in each of the main components of anthropometric features after rotation showed that the main parameters related to anthropometric characteristics in female handball players are: height, weight, knee-to-ground height, head width, Head circumference, waist circumference, leg length, ankle width, scapular fat, and biceps fat; in female volleyball players are: height, weight, trunk width at the navel, sitting pelvis width, elbow circumference, knee circumference, foot arc circumference, leg length, biceps fat, triceps fat; in female basketball players are: height, elbow circumference, head width, trunk circumference at chest level, trunk circumference at navel level, leg length, ankle width, scapular fat, and abdominal fat; and in players of the three groups of athletes are: height, knee-to-ground height, elbow circumference, head circumference, waist circumference, trunk circumference at chest level, scapular fat and maximum forearm circumference. Conclusion: The height is the leading standard index between different female handball, volleyball, and basketball players. Most of the anthropometric characteristics are various, related to the type of sport. Also, the biomechanical characteristics vary according to the unique skills in each discipline. In some sports, the biomechanical factors vary due to the features of the common sport and the design of specific training programs. Every sport needs to evaluate and study the anthropometric and biomechanical aspects of individuals.